Antifungal and antibacterial activity of some microalgae collected from lake "La Izvor" (Chisinau) - Olga ȚURCAN; Tamara SÎRBU; Valerina SLANINA (ACROSS)
Antibacterial and antifungal activity of 8 isolated microalgae strains from Lake "La Izvor" (Chisinau) was studied. Ethanolic biomass extracts were tested against five strains of pathogenic bacteria and fungi. Thus, according to the results of the experiments, the isolated strains of microalgae are able to synthesize metabolites that have antifungal and antibacterial activity against the tested phytopathogens. It should be noted that the obvious antibacterial activity showed the strains of Chlorella vulgaris, Oscillatoria planctonica and Spirulina major with the largest areas of inhibition of the growth of pathogenic bacteria Bacillus subtilis B-117, Xanthomonas campestris 8003b and Erwinia caratovora 8982.